Chromosomal aberrations in environmentally exposed population in relation to metabolic and DNA repair genes polymorphisms - Šrám, Radim J; Beskid, Olena; Binková, Blanka; Chvátalová, Irena; Lněničková, Zdena; Milcová, Alena; Solanský, Ivo; Tulupova, Elena; Bavorová, Hana; Očadlíková, Danuše; Farmer, Peter B (Mutation research. Fundamental and molecular mechanisms of mutagenesis, 2007)
The capital city of Prague is one of the most polluted localities of the Czech Republic. Therefore, the effect of exposure to carcinogenic polycyclic aromatic hydrocarbons (c-PAHs) adsorbed onto respirable air particles (<2.5mum) on chromosomal aberrations was studied in a group of policemen (males, aged 22-50 years) working in the downtown area of Prague and spending daily >8h outdoors (N=53). Age- and sex-matched healthy volunteers spending >90% daily time indoors were chosen as controls (N=52). Ambient air particles (PM10, PM2.5) and c-PAHs were monitored using versatile air pollution sampler (VAPS), and personal exposure was evaluated using personal samplers during working shift. Chromosomal aberrations were analyzed by conventional cytogenetic analysis and fluorescent in situ hybridization (FISH). Urinary cotinine plasma levels of vitamins A, E and C, folate, total cholesterol, HDL, LDL cholesterols and triglycerides were also analyzed as possible effect modifiers. Genotypes CYP1A1*2A, CYP1A1*2C, GSTM1, GSTP1, GSTT1, EPHX1, NAT2, hOGG1, XRCC1, XPD, p53 BstI, p53 MspI, MTHFR677, and MS2656 were determined by PCR-based RFLP assays. The following levels of air pollution were recorded during the study period (mean from HiVol sampling): PM10 62.6microg/m(3), c-PAHs 24.7ng/m(3), B[a]P 3.50ng/m(3). The conventional cytogenetic analysis did not reveal any differences between the group of policemen exposed to the ambient air pollution and the control group. The cytogenetic analysis by FISH analysis used the whole chromosome painting probes for chromosomes #1 and #4 (Cambio, UK). It detected a significant increase in all studied endpoints in the policemen compared to controls (% AB.C.=0.33+/-0.25 versus 0.24+/-0.18, p<0.05, F(G)/100=1.72+/-1.57 versus 1.25+/-1.11, p<0.05, AB/1000 (aberrations/1000 cells)=5.58+/-4.62 versus 3.90+/-3.06, p<0.05). CYP1A1*2C (Ile/Ile), XPD 23 (Lys/Lys), and XPD 6 (CC) genotypes were associated with an increase of aberrant cells by conventional method. Factors associated with an increased level of translocations by FISH included age, smoking, B[a]P-like DNA adducts (corresponding to the exposure of c-PAHs), folate, polymorphisms of CYP1A1*2C, GSTP1, EPHX1, p53 MspI and MTHFR. Ambient air exposure to c-PAHs significantly increased FISH cytogenetic parameters in nonsmoking policemen. We may conclude that FISH indicates that the city policemen in Prague represent a group of increased genotoxic risk. This is the first study that has reported a relationship between DNA adducts (biomarker of exposure) and chromosomal aberrations by FISH (biomarker of effect).
Keywords: dospělí; látky znečišťující vzduch; pracovní expozice; Air Pollutants; Glutathione Transferase; Carcinogens, Environmental; Humans; malování chromozomů; hybridizace in situ fluorescenční; lidé středního věku; Occupational Exposure; Middle Aged; Polycyclic Aromatic Hydrocarbons; Genotype; In Situ Hybridization, Fluorescence; Financing, Organized; financování organizované; cytochrom P-450 CYP1A1; Polymorphism, Genetic; mužské pohlaví; polymorfismus genetický; Chromosome Painting; Cytochrome P-450 CYP1A1; karcinogeny životního prostředí; Adult; Chromosome Aberrations; policie; genotyp; lidé; polycyklické aromatické uhlovodíky; Police; DNA Repair; oprava DNA; Male; chromozomální aberace; glutathiontransferasa